Mothers’ reactions to disclosures of sibling sexual abuse - Lafleur, Camille Tulia (Kansas State University, 2009)
This qualitative research study explored how mothers reacted to sibling sexual abuse disclosures while investigating the treatment and supportive services they engaged in to help them cope with this family trauma. Previous research focused on the role mothers played in intrafamilial sexual abuse cases, indicating that mothers were collusive and aware that the sexual abuse was occurring and did not intervene or protect their daughters. This research study’s purpose was to begin the foundational process of filling the gap in the literature concerning mothers and sibling sexual abuse disclosures. Qualitative data from the interviews conducted with mothers of sibling sexual abuse cases were utilized for this study. Participants were asked to reflect upon their early childhood experiences, characteristics of relationships in their families, how they handled the sibling sexual abuse disclosure, their level of functioning after the abuse disclosures, and any treatment strategies utilized, as well as their perceived effectiveness. The study shared the lived experiences of mothers who had sibling sexual abuse disclosures occur within their immediate families. The results revealed that the participants’ immediate reactions were not indicative of the action they took, following the disclosure, to protect their daughters from further abuse. Also indicated was a connection between mothers’ ability to cope with the abuse disclosure over time and their daughters’, the victims’, ability to make progressive steps towards improved functioning, following the abuse disclosure. This research can assist clinicians in understanding the importance of the therapeutic relationship and being sensitive to the delicate role mothers of perpetrators and victims have to play in these cases. In addition, clinicians must assist these mothers in transitioning through their numerous emotions, in order to return to a functional level of interaction in their lives.
Keywords: Sibling sexual abuse; Mothers' reactions to abuse; Health Sciences, Mental Health (0347)